Penilaian Kinerja Dosen Menggunakan Metode TOPSIS (Studi Kasus : Amik Mitra Gama) - Candra Surya (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
To improve the quality or performance of lecturers need an assessment. Assessment of lecturers can be done by Leaders and Chairman of Study Program such as assessment of Teaching, Research, Dedication, Responsibility, Personality, Loyalty, Cooperation, Leadership. Problems that have occurred so far to assess the performance of lecturers are still not optimal because there is no system / method used for assessment. It is therefore necessary to making a decision support system using the Technique For Other Reference by Similarity to Ideal Solution (TOPSIS). This method is able to choose the best alternative from the existing alternative. The alternative is the lecturer who will be assessed it’s performance. The result obtained by using this method is to know the lecturer who has the best performance. The best lecturers' determination will be issued in the form of numerical values and sorted by the largest value to the smallest value. From 5 alternative lecturers that have been tested are Lecturer 1, Lecturer 2, Lecturer 3 Lecturer 4 and Lecturer 5, then selected Lecturer 2 which has the best performance with a preference value of 0.5341.